2015
DOI: 10.2503/hortj.mi-055
|View full text |Cite
|
Sign up to set email alerts
|

Production of <i>Tomato Yellow Leaf Curl Virus</i>-free Parthenocarpic Tomato Plants by Leaf Primordia-free Shoot Apical Meristem Culture Combined with <i>in vitro</i> Grafting

Abstract: Tomato yellow leaf curl virus (TYLCV) infections result in decreased tomato growth and reduced yields, and the production is almost entirely lost if plants are infected during early growth. 'Kyo-temari' is the commercial name for the parthenocarpic tomato 'MPK-1', which has been vegetatively propagated and distributed to local farmers in Kyoto City for commercial cultivation. During the winter of 2013, the typical yellow leaf curl symptoms of TYLCV were observed in 10 parthenocarpic tomato cultivars, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Cloning and sequence determination of the full-length DNA B using rolling circle amplification The DNA extracted from a B6 pepper leaf sample, from which we previously recovered a full-length DNA A sequence of TYLCKaV (Koeda et al, 2016), was used to amplify a full-length DNA B sequence using a rolling circle amplification (RCA)-based TempliPhi DNA amplification kit (GE Healthcare, UK) according to Koeda et al (2015). The concatemers produced in the reaction were monomerized by restriction digestion with BamHΙ.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cloning and sequence determination of the full-length DNA B using rolling circle amplification The DNA extracted from a B6 pepper leaf sample, from which we previously recovered a full-length DNA A sequence of TYLCKaV (Koeda et al, 2016), was used to amplify a full-length DNA B sequence using a rolling circle amplification (RCA)-based TempliPhi DNA amplification kit (GE Healthcare, UK) according to Koeda et al (2015). The concatemers produced in the reaction were monomerized by restriction digestion with BamHΙ.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, TYLCV species of the genus Begomovirus cause the most devastating emerging disease that affects tomatoes worldwide (Czosnek, 2007). Since the first report of tomato yellow leaf curl disease in Japan in 1996 (Kato et al, 1998), TYLCV has been reported in 37 out of 47 prefectures, mainly in the southwest, which has a relatively warm climate (Hanada, 2012;Koeda et al, 2015). During this period, a wide variety of distinct local begomovirus species have been identified in solanaceous crops in Southeast and East Asia; however, TYLCV has not been found there (Kenyon et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that tomato plant grown under different combinations of LED light has a confrontation to the various diseases and pathogen attack [21]. Plenty of research has already been done on tomato in vitro culture [22][23][24]. However, information on the effect of a combination of artificial R and B LED light application on in vitro tomato plantlets is still inadequate so far.…”
Section: Introductionmentioning
confidence: 99%
“…Amplification of full-length viral genomes of DNA A and DNA B was conducted according to the protocol of Koeda et al (2015) by a RCA reaction. Nucleotide sequencing was performed using an ABI PRISM 3100 genetic analyzer with an ABI PRISM BigDye Terminator v3.1 Cycle Sequencing Kit (Applied Biosystems).…”
Section: Viral Dna Detection and Sequence Analysismentioning
confidence: 99%